THE POSSIBILITY OF CREATING A SYNTHETIC S-VELOCITY MODEL BY RECALCULATING THE P-VELOCITY MODEL - Shumlianska, L.; Dubovenko, Yu.; Pigulevskiy, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem of limited and incomplete seismological data leads to significant distortions in design models based on primary seismological models. One of the reasons for the incompleteness of the primary seismological data is the significant predominance of these definitions of P phase arrivals of body waves in comparison with the registration of S-wave arrivals. In this regard, the question arises about the statistical proportionality (significance) and correspondence of the velocity models obtained from the arrivals of P- and S-waves. As part of the solution of this problem, the authors studied the possibility of recalculating the P-velocity model into a synthetic velocity model of S-waves to assess its similarity to the experimental model. The article shows that the deviations of the synthetic model of S-wave velocities from the measured curve are comparable with the accuracy of the methods by which these velocity models were obtained, therefore, the obtained synthetic model of S-waves can be used to construct structural models of the mantle. We proposed our own approach to solving the problem of obtaining a synthetic S-velocity model because of recalculation of the P-velocity model and showed that when recalculated, using the arithmetic mean of five reference seismological models of the Vp/Vs ratio, the synthetic S-velocity model has acceptable deviations comparable to the resolution ability of the method of obtaining them. As the results of determining the velocity errors when using the kinematic method of the Taylor approximation show, with errors in determining the maximum depth of the apparent velocity of the refracted ray 0  ( ) q = 6; 7; 8 km, the calculated velocity errors are of the same order as the deviations for one-dimensional models, and significantly less than the error of ± 0.1 km / s, which is achieved by other seismic methods. The synthetic S-velocity model obtained because of the recalculation of the P-velocity model has the property of proportionality with the original model, which gives advantages in accuracy in the further joint use of two collinear models (P, S) when converting to physico-lithological models of the mantle.
Keywords: synthetic S-wave model; correction; cinematic method of seismic tomography